Factors to be considered in determining the amount of compensation in land acquisition for infrastructure project / Nurul Amni Abdullah and Nor Nazihah Chuweni - Abdullah, Nurul Amni; Chuweni, Nor Nazihah (2019)
The study determined the amount of compensation in land acquisition for infrastructure project. The main issue in land acquisition is the affected landowners who are not satisfied with the amount of compensation given by the government. The study is supported with two court cases of land acquisition for infrastructure project in Kelantan. The project is the development of road project namely East Coast Economic Region (ECER) from Gua Musang, Kelantan to Kampung Relong, Pahang. The aim of the study is to identify the factors to be considered in determining the amount of compensation in land acquisition for infrastructure project and factors of contributing dissatisfaction to the landowners toward the amount of compensation in land acquisition. Qualitative method is employed through interviews with government and private valuers. The findings show that the factors in determining the compensation in land acquisition in Malaysia follow the first schedule of Land Acquisition Act 1960 namely market value, betterment, severance, injurious affection, disturbance claims and accommodation works. On the other hand, the factors of dissatisfaction to the landowners toward amount of compensation in Malaysia is inadequate amount of compensation.